"Convinced that God had called us" : dreams, visions, and the perception of God's will in Luke-Acts - Miller, John B. F. (Biblical interpretation series,, 2007)
Dream and vision scenes figure prominently in Luke-Acts. Following a discussion of methodology, historical background, and critical scholarship, this study provides a comprehensive examination of the dreams and visions in the Lukan narrative. Special attention is given to those scenes that feature significant interpretation by characters in the story (e.g., Zechariah and Mary [Luke 1-2], Saul's/Paul's conversion [Acts 9, 22, and 26], the Cornelius-Peter episode [Acts 10:1-11:18], and Paul's dream at Troas [Acts 16:9-10]). While a number of studies have highlighted the importance of dreams and visions for Luke's portrayal of God, the present study suggests that the human side of these visionary encounters is equally important. Just as Lukan dreams and visions depict God's active involvement in the events of human history, they also depict God's people attempting to perceive God's will through these visionary encounters.